1995
DOI: 10.1073/pnas.92.6.2375
|View full text |Cite
|
Sign up to set email alerts
|

Negative transcriptional regulation in anergic T cells.

Abstract: Anergy is a mechanism of T-lymphocyte tolerance induced by antigen-receptor stimulation in the absence of costimulation, whereby T cells exhibit a defect in antigen-induced transcription of the interleukin 2 (IL-2) gene. Here we present evidence for a mechanism of negative IL-2 gene regulation in anergic T cells. High amounts of binding activity to the negative regulatory element A (NRE-A) of the IL-2 promotor were detected in nuclear extracts from human T cells shortly after induction of anergy. Rapid inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 20 publications
1
34
1
Order By: Relevance
“…Therefore, we favor a model where T cell anergy would be maintained by a cell autonomous mechanism. Interestingly, using T cell clones, accumulating evidence suggests that anergy in vitro could be maintained by a dominant-acting repressor molecule that inhibits IL-2 signal transduction (23)(24)(25)(26)(27). Whether a similar mechanism is responsible for SEB-induced T cell anergy in vivo remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we favor a model where T cell anergy would be maintained by a cell autonomous mechanism. Interestingly, using T cell clones, accumulating evidence suggests that anergy in vitro could be maintained by a dominant-acting repressor molecule that inhibits IL-2 signal transduction (23)(24)(25)(26)(27). Whether a similar mechanism is responsible for SEB-induced T cell anergy in vivo remains to be investigated.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that antibody-mediated anergy may be qualitatively different than anergy induced in response to B7 lo APCs, despite inducing similar biochemical alterations in Ras, Rap1, and ERKs. Additional negative regulation of the IL-2 gene at the promoter level independent of upstream signaling has been shown (52)(53)(54). Such additional blocks in anergic cells were invoked by Crespi et al (22) who showed that ERK activation via expression of a constitutively active mutant of Ras was not sufficient to prevent anti-CD3 antibody-induced anergy.…”
Section: Antibody-induced Anergy Cannot Be Prevented By B-raf Expressmentioning
confidence: 99%
“…Anergic T cells appeared to have a defect in signaling pathways upstream of transcription of the IL-2 gene (4 -6). Additional studies demonstrated the presence of cis-dominant negative regulatory elements affecting IL-2 transcription (7,8). The recent finding of increased general receptor of phosphoinositides-1 expression indicated that broader genetic changes may accompany the induction and maintenance of the anergic phenotype (9).…”
mentioning
confidence: 99%